Caracterización fisiográfica y morfométrica de la cuenca hidrográfica del río chone como aporte a la gestión integral de los recursos hídricos - Burgos Velásquez, Jorge Andrés (2016)
The research presents the physiographic and morphometric characterization of the watershed of Chone River, by calculating parameters and morphometric indexes representing numerically typologies by form and relief of the basin, giving drainage characteristics, shape and relief; with the development of water balance by isohyets and isotherms, both graphically represented in thematic maps that will serve as a contribution for further comprehensive management of water resources. The research use a field quantitative method; besides processing numerical and spatial information, field testing was done with sampling points to obtain data. For the topography, cartography and morphometry analysis data from the Global Data Explorer by Geobrain and the National Information System were used, analyzed in Geographic Information Systems (GIS) programs by Google Earth and Bing Maps basemaps corrected by the points that were used for reference; for physiograph weather network data of the National Meteorology and Hydrology Institute of (INAMHI) were used. The basin has an elongated shape, with an average gradient of 12.5% and a drainage density of 0.35 km ⁄ km2 and most of the surface 2201.78 Km2 surface has water deficit so it can be considered a failure basin Water. The soil type corresponds to the order Vertisol and 16.58% of the total basin has a 70% usage of cultivated grass and 30% of short-cycle crops.